Root caries : from prevalence to therapy - Allen, Patrick Finbarr 1965-; Alves, Luana Severo; Banerjee, Avijit; Bedran-Russo, Ana K.; Boukpessi, Tchilalo 1979-; Carrilho, Marcela Rocha de Olivera (Basel : Karger, 2017)
Case reports and clinical trials conducted in various countries show, more and more frequently, a positive correlation between the presence of original teeth and prevalence of root caries in older age. Because this is a global trend, it is likely that the predicted increase in the worldwide elderly population may soon cause a significant increase in the number of people requiring effective means of preventing and treating root surface caries. In response to this development, a team of outstanding contributors has reviewed the most important aspects of root caries. This new volume presents their findings along with discussions of how to deal with this health issue that progressively affects the oral health balance. The chapters in this book are divided in four core parts: Epidemiology, Biological Determinants, Lesion Assessment and Features and Preventive and Operative Therapies. The collection of state-of-the-art articles provides a broad overview and will serve as a reference for clinicians as well as scientists and, hopefully, will encourage new research.
La función de los autores fue determinada por el catalogador
Keywords: CARIES RADICULAR; CARIES RADICULAR -- TRATAMIENTO